Corporate governance in startups: a classification model for agtechs in Brazil - Felipe Urtado; Cláudio Machado Filho (Cogent Business & Management, 2025)
This article explores the evolution of corporate governance practices in agtech startups across various stages of the life cycle: ideation, validation, traction, scalability, and maturity. Based on a systematic literature review that initially identified 496 articles, subsequently refined to 4 main studies, and empirical research conducted with founders and CEOs of Brazilian agtechs, this study proposes a new classification model adapted to the Brazilian context. The results indicate that the formalization of governance practices can be facilitated by a structured model that emphasizes internal organization, product development, risk governance, and sustainability. In addition to enhancing transparency and talent retention, the proposed model highlights the importance of adapting governance practices to the specific needs of each development stage. This work uniquely contributes to the literature by directly linking governance practices to the needs of startups in emerging sectors, providing a validated framework with practical implications for managers and policymakers and suggesting directions for future research.